Developing and validating rapid assessment instruments - Abell, Neil.; Springer, David W.; Kamata, Akihito (New York ; Oxford : Oxford University Press, 2009)
This pocket guide provides a comprehensive start-to-finish overview of the basics of scale development, giving practical guidance that practitioners at all levels will be able to put to use.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Psychological tests; Psychometrics; Social service